2013
DOI: 10.1002/lary.24417
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous injection laryngoplasty

Abstract: Level of Evidence NA Laryngoscope, 124:742–745, 2014

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 16 publications
1
39
0
Order By: Relevance
“…Whereas material backing out was not observed in our testing, a better understanding of injection mechanics and the effects of needle orientation and material temperature characteristics might better inform clinical use of these materials. These materials vary in their resorption rate and viscosity, with HA being the least viscous material, easiest to inject, and becoming progressively more viscous and longer acting from CMC to CaHA . Our results identified that HA requires the least amount of force to complete the injection from start to finish.…”
Section: Discussionmentioning
confidence: 74%
“…Whereas material backing out was not observed in our testing, a better understanding of injection mechanics and the effects of needle orientation and material temperature characteristics might better inform clinical use of these materials. These materials vary in their resorption rate and viscosity, with HA being the least viscous material, easiest to inject, and becoming progressively more viscous and longer acting from CMC to CaHA . Our results identified that HA requires the least amount of force to complete the injection from start to finish.…”
Section: Discussionmentioning
confidence: 74%
“…In particular, an accurate localization of the needle is very tricky, and most laryngologists identify the position of the needle tip indirectly by the distortion of vocal fold configuration. Finally, because of the above‐mentioned reasons, accurate localization requires a high level of experience, and there is a steep learning curve involved in mastering this technique . Also, there are several limitations from the perspective of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional insertion area in VFI using the CT approach is 5 to 12 mm from the midline just below the inferior border of the thyroid cartilage . During VFI via CT approach without the device, the route of the needle tip might be ambiguous and usually is presumed by an anatomical imaginary line or a change of vocal fold configuration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, Chhetri and Jamal reported their approach to percutaneous vocal fold injection via the transcricothyroid membrane (TCM) and transthyroid cartilage approaches with concurrent flexible transnasal endoscopic monitoring . These investigators identified that it was necessary to develop expertise in correlating external landmarks with internal laryngeal anatomy for these blind approaches and that a “certain learning curve” is needed to master this technique . For transcricothyroid injection, Clary et al similarly identified that “precise placement of the needle tip is more difficult to obtain and can require a significant level of experience.”…”
Section: Discussionmentioning
confidence: 99%